The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/chem.201503616
|View full text |Cite
|
Sign up to set email alerts
|

Steric Constraints Induced Frustrated Growth of Supramolecular Nanorods in Water

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 91 publications
4
55
0
1
Order By: Relevance
“…This is a good indication that the neutral Phe‐His‐Phe‐His‐Phe based oligopeptide induces the self‐assembly into ordered supramolecular structures, whereas protonation at a pH close to the p K a value of the isolated histidine amino acid side group of 6.0, leads to the disassembly due to Coulomb repulsion between the assembled aromatic oligopeptide backbone. In the past, we have been able to use CD spectroscopy in combination with cryogenic transmission electron microscopy (cryo‐TEM), small angle X‐ray scattering (SAXS), and diffusion‐based PFG‐NMR experiments, to correlate spectroscopic changes with a supramolecular monomer to polymer transition . The small difference in the pH‐induced transition of 1 compared to 2 of 0.7 pH units, is an indication that the high surface charge density of cationic 2 leads to a slightly less stable polymer and hence more favorable disassembly at lower H + concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a good indication that the neutral Phe‐His‐Phe‐His‐Phe based oligopeptide induces the self‐assembly into ordered supramolecular structures, whereas protonation at a pH close to the p K a value of the isolated histidine amino acid side group of 6.0, leads to the disassembly due to Coulomb repulsion between the assembled aromatic oligopeptide backbone. In the past, we have been able to use CD spectroscopy in combination with cryogenic transmission electron microscopy (cryo‐TEM), small angle X‐ray scattering (SAXS), and diffusion‐based PFG‐NMR experiments, to correlate spectroscopic changes with a supramolecular monomer to polymer transition . The small difference in the pH‐induced transition of 1 compared to 2 of 0.7 pH units, is an indication that the high surface charge density of cationic 2 leads to a slightly less stable polymer and hence more favorable disassembly at lower H + concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…These combine high robustness and fidelity in the self‐assembly with stimuli‐responsive properties toward pH‐values of the surrounding medium. We have previously reported C 3 ‐symmetrical nonaphenylalanine supramolecular building monomers equipped with dendritic tetraethylene glycol chains, with binding affinities of up to 7 × 10 7 m −1 in water . In order to introduce pH‐switchable properties into the supramolecular polymerization, we changed the peripheral dendritic tetraethylene glycol chains for dendritic carboxylic acids in the amphiphilic monomers that are highly charged and thus molecularly dissolved at neutral pH and self‐assemble into anisotropic supramolecular polymers by acidifying the aqueous medium .…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the high robustness of the oxidation damage repair and substrate promiscuity of this class of reductases. [12,18] We further relied on their steric demand and high chain flexibility to introduce repulsive forces in the supramolecular polymerization process,which prevents the formation of infinitely long polymers,aprocess we usually refer to as frustrated growth. [12,18] We further relied on their steric demand and high chain flexibility to introduce repulsive forces in the supramolecular polymerization process,which prevents the formation of infinitely long polymers,aprocess we usually refer to as frustrated growth.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[324][325][326][327][328] Importantly, repulsive contributions in supramolecular systems and polymers can also be based on steric constraints, as reported by Stupp, 329 Lee, 330 Hedrick, 331 Fernandez, Schacher, 332 and Besenius. 333 The lack of charges in hydrophilic dendritic oligoethylene glycol end groups for example simplified mechanistic investigations and thermodynamic characterization of the supramolecular polymers in water. In phenylalanine-rich monomers, the concentration-dependent degree of polymerization and contour length of the nanorod-like polymers was determined from SAXS, PFG-NMR and cryo-TEM experiments and could be correlated with the binding affinities of up to 7 3 10 7 M 21 in phosphate buffer, which were determined using titration experiments.…”
mentioning
confidence: 99%
“…In phenylalanine-rich monomers, the concentration-dependent degree of polymerization and contour length of the nanorod-like polymers was determined from SAXS, PFG-NMR and cryo-TEM experiments and could be correlated with the binding affinities of up to 7 3 10 7 M 21 in phosphate buffer, which were determined using titration experiments. 333 More recently, the Besenius group has shown that by using a very hydrophobic hexapeptide, based on phenylalanine alternated with a charged amino acid, in the side arms of either of the comonomers which were further equipped with dendritic tetra(ethylene glycol) chains, a pH-regulated selectivity in the formation of a heterocopolymer and the acidic or basic homopolymer was achieved (Fig. 24).…”
mentioning
confidence: 99%